William Wordsworth’s Overcoming Life’s Struggles in ‘Intimations of Immortality’ Poems - Hendriani, Ria (Journal of English Language and Education, 2024)
This study explores how William Wordsworth addresses and overcomes personal and existential problems in his poem Intimations of Immortality from Early Childhood, a pivotal work in Romantic literature. The poem explores themes of memory, spiritual transcendence, and the transition from childhood to adulthood. There is a gap in understanding how Wordsworth uses them to confront his own struggles. The purpose of this study is to investigate how Wordsworth transforms personal challenges into sources of solace and insight. Through close textual analysis, the study highlights Wordsworth’s use of the divine essence of childhood and nature as stabilizing forces that help him cope with personal loss and disillusionment. The findings suggest that childhood memories and nature offer enduring comfort, providing a philosophical framework for managing life’s difficulties. The study concludes that Wordsworth’s poetry serves as a powerful tool for emotional and spiritual growth, showcasing the transformative power of introspection.